A redox-based mechanism for the contractile and relaxing effects of NO in the guinea-pig gall bladder - Alcón, Soledad (Blackwell Science Inc, 2001)
1. The purpose of this study was to determine the effects of sodium nitroprusside (SNP), 2,2′-(hydroxynitrosohydrazino)bis-ethanamine (DETA/NO) and 3-morpholinosydnonimine (SIN-1), NO donors which yield different NO reactive species (NO(+), NO. and peroxynitrite, respectively), as well as exogenous peroxynitrite, on gall bladder contractility. 2. Under resting tone conditions, SNP induced a dose-dependent contraction with a maximal effect (10.3 ± 0.7 mN, s.e.m.) at 1 mm. Consistent with these findings, SNP caused a concentration-dependent depolarization of gall bladder smooth muscle. The excitatory effects of SNP were dependent on extracellular calcium entry through L-type Ca(2+) channels. Furthermore, the contraction and depolarization were sensitive to tyrosine kinase blockade, and an associated increase in tyrosine phosphorylation was detected in Western blot studies. 3. DETA/NO induced dose-dependent relaxing effects. These relaxations were sensitive to the guanylyl cyclase inhibitor 1H-[1,2,4]oxidiazolo[4,3-a]quinoxaline-1-one (ODQ, 2 μm) but they were not altered by treatment with the potassium channel blockers tetraethylammoniun (TEA, 5 mm) and 4-aminopyridine (4-AP, 5 mm). 4. When tested in a reducing environment (created by 2.5 mm 1,4-dithiothreitol, DTT), SNP caused a relaxation of gall bladder muscle strips. Similarly, the SNP-induced contraction was converted to a relaxation, and associated hyperpolarization, when DTT was added during the steady state of an SNP-induced response. 5. SIN-1 (0.1 mm), which has been shown to release peroxynitrite, induced relaxing effects that were enhanced by superoxide dismutase (SOD, 50 U ml(−1)). The relaxations induced by either SIN-1 alone or SIN-1 in the presence of SOD were strengthened by catalase (1000 U ml(−1)) and abolished by ODQ pretreatment. However, exogenous peroxynitrite induced a concentration-dependent contraction, which was dependent on activation of leukotriene (LT) metabolism and extracellular calcium. The peroxynitrite-induced contraction was abolished in the presence of the peroxynitrite scavenger melatonin. These results suggest that SIN-1 behaves as an NO. rather than a peroxynitrite source. 6. We conclude that, depending on the redox state, NO has opposing effects on the motility of the gall bladder, being a relaxing agent when in NO. form and a contracting agent when in NO(+) or peroxynitrite redox species form. Knowledge of the contrasting effects of the different redox forms of NO can clarify our understanding of the effects of NO donors on gall bladder and other smooth muscle cell types.